#### Answer

(5x+y)(2x-3y)

#### Work Step by Step

10$x^{2}$ -13xy -3$y^{2}=10$x^{2}$ -15xy+2xy -3$y^{2}$=
5x(2x-3y)+y(2x-3y)=(5x+y)(2x-3y)

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

(5x+y)(2x-3y)

10$x^{2}$ -13xy -3$y^{2}=10$x^{2}$ -15xy+2xy -3$y^{2}$=
5x(2x-3y)+y(2x-3y)=(5x+y)(2x-3y)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.